Chronic wounds and adaptive Pseudomonas aeruginosa: A phenotypic and genotypic characterization - Kasandra Buchholtz; Rie Jønsson; Rasmus L. Marvig; Biljana Mojsoska; Karen Angeliki Krogfelt (Current Research in Microbial Sciences)
Phenotypic and genetic diversity is found in varying prevalence in clinical populations where beneficial adaptations enable the bacteria to avoid recognition and eradication by the host immune system. This study aimed to investigate the presence of Pseudomonas aeruginosa in chronic venous leg ulcers wounds over an 8-week time course. This was performed using genomic and phenotypic approaches to understand the survival and persistence of Pseudomonas strains. The findings of this study show that the two patients were colonized with a recurring P. aeruginosa genotype with only minor phenotypic differences and few SNP differences, suggesting that the Pseudomonas isolates present in the wound can survive and proliferate in the host's hostile environment. The results provided from this study will allow us to understand P. aeruginosa colonization during a 8 week time period.